2020
DOI: 10.1007/s10822-020-00360-8
|View full text |Cite
|
Sign up to set email alerts
|

QSAR and molecular docking for the search of AOX inhibitors: a rational drug discovery approach

Abstract: The alternative oxidase (AOX) is a monotopic diiron carboxylate protein that catalyses the oxidation of ubiquinol and the reduction of oxygen to water. Although a number of AOX inhibitors have been discovered, little is still known about the ligand–protein interaction and essential chemical characteristics of compounds required for a potent inhibition. Furthermore, owing to the rapidly growing resistance to existing inhibitors, new compounds with improved potency and pharmacokinetic properties are urgently req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The remaining residues, R118, L122 and T219, resulted in a complete eradication of inhibitor potency, implying they are involved with keeping the semiquinone radical bound during the transition state. This is inline with recent protein ligand interaction fingerprint (PLIF) experiments, which suggested that these are the most important residues when it comes to inhibitor interactions, and are therefore the most likely candidates to be stabilising the semi-quinone intermediate [34]. However, only the T219 mutants altered the docking score as well, indicating it is the only residue that fully interacts with both the substrate and its transition state.…”
Section: Discussionsupporting
confidence: 80%
“…The remaining residues, R118, L122 and T219, resulted in a complete eradication of inhibitor potency, implying they are involved with keeping the semiquinone radical bound during the transition state. This is inline with recent protein ligand interaction fingerprint (PLIF) experiments, which suggested that these are the most important residues when it comes to inhibitor interactions, and are therefore the most likely candidates to be stabilising the semi-quinone intermediate [34]. However, only the T219 mutants altered the docking score as well, indicating it is the only residue that fully interacts with both the substrate and its transition state.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, such results indicate that CB and CD are broad-spectrum AOX inhibitors, while AF and AC are slightly more selective toward TAO. A comparison of their chemical structures reveals that those four compounds have identical pharmacophores but different tail substituents (Young et al, 2020;Rosell-Hidalgo et al, 2021). While CB and CD have pure isoprenoid tails, AC and AF contain substituted six-atom and five-atom rings at the end of the isoprenoid tail, respectively, which might restrict interaction with the protein ligand-binding site in plant AOXs due to a narrower entrance into the hydrophobic cavity than calculated for TAO (May et al, 2017).…”
Section: Proteinsmentioning
confidence: 97%
“…Compounds was also reported to show specific inhibitory effect toward mitochondrial cytochrome bc1 complex [109] and a recombinant AOX inhibitor expressed in E. coli membranes 7.4 ± 3 nM [110].…”
Section: Monocyclic Typementioning
confidence: 98%
“…Potent inhibitory activity of trypanosomal glycerol kinase and TAO of T. b. brucei for 22 were described in 2019 105 . In addition, 22 and 33 showed inhibitory activity against Cryptosporidium parvum AOX (alternative oxidase) with IC 50 values of 0.3 and 500 nM, respectively 68 , potent sensitivity of recombinant Sauromatum guttatum AOX with IC 50 values of 0.06 and 7 nM and native Arum maculatum AOX with IC 50 values of 0.16 and 70 nM 106 , 107 , 108 ; 33 was also reported to show specific inhibitory effect toward mitochondrial cytochrome bc1 complex 109 and a recombinant AOX inhibitor expressed in E. coli membranes 7.4 ± 3 nM 110 .…”
Section: Overviewmentioning
confidence: 99%